Former Very Preterm Infants Show an Unfavorable Cardiovascular Risk Profile at a Preschool Age - Posod, Anna (PLoS One, 2016)
Cardiovascular disease is the leading cause of death worldwide. Evidence points towards an unfavorable cardiovascular risk profile of former preterm infants in adolescence and adulthood. The aim of this study was to determine whether cardiovascular risk predictors are detectable in former very preterm infants at a preschool age. Five- to seven-year-old children born at <32 weeks’ gestational age were included in the study. Same-aged children born at term served as controls. Basic data of study participants were collected by means of follow-up databases and standardized questionnaires. At study visit, anthropometric data, blood pressure readings and aortic intima-media thickness were assessed. Blood samples were obtained after an overnight fast. In comparison to children born at term, former preterm infants had higher systolic and diastolic blood pressure readings (odds ratio [95% confidence interval] per 1-SD higher blood pressure level 3.2 [2.0–5.0], p<0.001 and 1.6 [1.1–1.2], p = 0.008), fasting glucose levels (OR [95% CI] 5.2 [2.7–10.1], p<0.001), homeostasis model assessment index (OR [95% CI] 1.6 [1.0–2.6], p = 0.036), and cholesterol levels (OR [95% CI] 2.1 [1.3–3.4], p = 0.002). Systolic prehypertension (23.7% vs. 2.2%; OR [95% CI] 13.8 [3.1–60.9], p = 0.001), elevated glucose levels (28.6% vs. 5.9%; OR [95% CI] 6.4 [1.4–28.8], p = 0.016), and hypercholesterolemia (77.4% vs. 52.9%; OR [95% CI] 3.0 [1.3–7.1], p = 0.010) were significantly more prevalent in the preterm group. As former very preterm infants display an unfavorable cardiovascular risk profile already at a preschool age, implementation of routine cardiovascular follow-up programs might be warranted.